2020
DOI: 10.1177/1756284819897531
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action and therapeutic benefit of rifaximin in patients with irritable bowel syndrome: a narrative review

Abstract: Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder with a multifactorial pathophysiology. The gut microbiota differs between patients with IBS and healthy individuals. After a bout of acute gastroenteritis, postinfection IBS may result in up to approximately 10% of those affected. Small intestinal bacterial overgrowth (SIBO) is more common in patients with IBS than in healthy individuals, and eradication of SIBO with systemic antibiotics has decreased symptoms of IBS in some patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 89 publications
(213 reference statements)
0
20
0
Order By: Relevance
“…According to some studies, Proteobacteria proliferation creates a state of dysbiosis and contributes to an increased risk of endogenous and exogenous infections [ 68 ]. Rifaximin, modulates the secretion of proinflammatory cytokines and, due to low oral bioavailability, has little effect on the composition of gut microbiota [ 69 ]. A meta-analysis of 26 randomized controlled trials of adults with small intestinal bacterial overgrowth (SIBO) signified a high rate of SIBO eradication with rifaximin [ 70 ].…”
Section: Intestinal Infections and Antibiotic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…According to some studies, Proteobacteria proliferation creates a state of dysbiosis and contributes to an increased risk of endogenous and exogenous infections [ 68 ]. Rifaximin, modulates the secretion of proinflammatory cytokines and, due to low oral bioavailability, has little effect on the composition of gut microbiota [ 69 ]. A meta-analysis of 26 randomized controlled trials of adults with small intestinal bacterial overgrowth (SIBO) signified a high rate of SIBO eradication with rifaximin [ 70 ].…”
Section: Intestinal Infections and Antibiotic Therapymentioning
confidence: 99%
“…A meta-analysis of 26 randomized controlled trials of adults with small intestinal bacterial overgrowth (SIBO) signified a high rate of SIBO eradication with rifaximin [ 70 ]. The accuracy mechanism of action of rifaximin in this case is likely multifactorial and more research is needed; but, in the USA and Canada, rifaximin is indicated in adults with IBS therapy [ 69 ]. The Enterobacteriaceae family, which is widely distributed in the intestines, also includes pathogenic strains of Escherichia coli or Klebsiella spp.…”
Section: Intestinal Infections and Antibiotic Therapymentioning
confidence: 99%
“…Reduced endotoxemia and altered microbiota-associated metabolic function, with a change in fatty acids production, have been reported following Rifaximin treatment 128 . Furthermore, it seems that the mechanism of action of Rifaximin, despite its role as a gastrointestinal-targeting antibiotic, might extend beyond the GM, modulating the production of inflammatory cytokines and intestinal permeability 133 . Finally, Rifaximin treatments have been seen to promote beneficial gut bacteria such as Bifidobacteria and Lactobacilli in patients with gastrointestinal and liver disorders 134 , 135 .…”
Section: Discussionmentioning
confidence: 99%
“…Rifaximin, a member of the rifamycin family and a nonsystemic antibiotic, has been approved for the treatments of travelers' diarrhea, hepatic encephalopathy, and irritable bowel syndrome without constipation (Lexicomp, 2021). Its clinical benefits were thought to be mediated through altered gastrointestinal (GI) microbiota or dysbiosis (Chey et al, 2020). Antibacterial evaluations of 15 against a representative panel of GI bacteria revealed similarities with rifaximin (Yuan et al, 2020).…”
Section: Hybrids Of Rifamycinsmentioning
confidence: 99%